Desclasificación de sectores urbanísticos: los informes pormenorizados como instrumento clave para la toma de decisiones en la administración urbanística - Izaskun Iriarte Irureta (Revista Vasca de Administración Pública)
The proposal to declassify urban development sectors is a thorny issue when land becomes undevelopable, and the possibility of the urban development administration being liable for damages arises. This paper presents the experience of the Vitoria-Gasteiz City Council of including the declassification of twenty-five sectors in the initial approval agreement of the revision of its General Urban Development Plan, a reasoned decision founded in law, based on the detailed and individualised reports on each of the sectors, and an external legal opinion of contrast.